2004
DOI: 10.5144/0256-4947.2004.437
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tuberculosis: CT and MRI features

Abstract: BACKGROUNDSpinal tuberculosis (TB) is perhaps the most clinically important extrapulmonary form of the disease. Early recognition is therefore necessary to minimize residual spinal deformity and/or permanent neurological deficit. We defined the CT and MRI image morphology of spinal TB and correlated the imaging features of these two modalities.METHODSCT (29 patients) and MRI (11 patients) images were retrospectively analyzed in 30 patients with proved spinal TB. CT and MRI findings were compared in cases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
45
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 24 publications
9
45
3
Order By: Relevance
“…This suggested that in the economically productive years of life, Pott's spine was more prevalent in females. The lower thoracic and the upper lumbar levels were found to be most commonly affected in most of the studies [1,2,8,10]. In our study, the lumbar vertebrae were most commonly affected, followed by the dorsal vertebrae, which was similar to the findings of Sinan et al [8].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This suggested that in the economically productive years of life, Pott's spine was more prevalent in females. The lower thoracic and the upper lumbar levels were found to be most commonly affected in most of the studies [1,2,8,10]. In our study, the lumbar vertebrae were most commonly affected, followed by the dorsal vertebrae, which was similar to the findings of Sinan et al [8].…”
Section: Discussionsupporting
confidence: 82%
“…In our study, most of the cases were between the ages of 21-50 years (mean 38.3 + 17.6), which was similar to the finding of Mirsaeidi et al, [9] who found a mean age of 39 + 16 years. Tuberculosis of the spine was found to be more common in males than in females in most of the previously published series [4,[8][9][10], although Osborn [7] suggested no gender predilection. We noted that although overall Pott's spine was more prevalent in males, in between 21-50 years of age in which Pott's spine was the most prevalent, there was a female predominance (55%).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The first and most common clinical symptom of Pott's disease is the back pain, followed with fever [13].…”
Section: Discussionmentioning
confidence: 99%